Studies on influence of seashell-based filler on water absorption behaviour of bamboo-epoxy composite: mechanical and fractured surface characterization (Fracture and Structural Integrity, 2025)
The hydrophilic nature of bamboo fiber makes them prone to moisture uptake and subsequent property degradation. In this study, bamboo fiber–epoxy composites were hybridized with clamshell-derived particulate fillers to mitigate the adverse effect of moisture absorption and enhance performance. Composites with 0, 3, 6, and 9 wt% filler were fabricated via compression molding technique. Moisture absorption and its influence on tensile and flexural strength were evaluated following ASTM standards. Results revealed that unfilled composites exhibited highest water uptake and severe strength loss upon moisture exposure, whereas filler addition reduced water uptake and improved strength retention. The 6 wt% filler showed optimal performance with 30.4% reduction in water uptake, 67.5% retention of tensile strength, and 70% retention of flexural strength. Fractography analysis confirmed the role of filler acting as a barrier against moisture ingress and restricting interfacial degradation.
Keywords: Bamboo Composites; Hybrid Composites; Biofiller; Seashell; Moisture absorption; Mechanical Properties